Can fall armyworm damage decrease depending on the season, maize hybrid, and type of pesticides? - Briones Ochoa, Mario Alberto (2023)
Maize is the third most important grass produced in the world after wheat and rice. Among the limitations of its production, fall armyworm, Spodoptera frugiperda Smith (Lepidoptera: Noctuidae) is considered the most relevant pest in which corn is the main host plant. During the dry and rainy seasons of 2021-2022, lots of 1200 m2 were planted including three commercial hybrids, ADV-9139, Trueno NB-7443, and INIAP-551 in which the treatments were evaluated: T1: Sequence of insecticides (CLE) based on chlorantraniliprole, lufenuron, and emamectin benzoate. T2: Biological insecticide based on Bacillus thuringiensis (BT). T3: Methomyl-based treatment (MET). T4: Untreated plot (UP). Plant and cob damage, plant height and cob insertion, and grain yield were evaluated, and an economic analysis was performed. The least damage to plants and cobs was detected in the ADV-9139 hybrid. Regarding pesticides, CLE showed the best damage control in plants and the cobs were less damaged when CLE and BT were applied. Plant height and cob insertion height were lower in the ADV-9139 hybrid in which the highest grain yields were estimated. Plots treated with BT showed the highest increase in grain yield. The results show that the management of this voracious insect can be achieved combining the partial resistance of a maize genotype with pesticide applications with the lowest social, economic and ecological costs.